Inhibition of intimal thickening after vascular injury with a cocktail of vascular endothelial growth factor and cyclic Arg-Gly-Asp peptide. (1st October 2016) - Li, Yue; McRobb, Lucinda S.; Khachigian, Levon M.
Abstract: Background: Percutaneous coronary intervention is widely used for the treatment of coronary artery disease; however, significant challenges such as restenosis remain. Key to solving these problems is to inhibit smooth muscle cell activation while enhancing re-endothelialization. Early growth response-1 (Egr-1) is a transcription factor that regulates vascular smooth muscle cell (SMC) proliferation and migration through its control of an array of downstream genes. Methods: A "cocktail" of vascular endothelial growth factor (VEGF)-A, VEGF-D and cyclic RGD was tested for its ability to inhibit neointima formation and accelerate re-endothelialization following balloon injury to carotid arteries of rats. Results: In vitro, the cocktail stimulated endothelial cell growth yet inhibited smooth muscle cell growth . In vivo, cocktail-treated injured arteries exhibited reduced intimal thickening by > 50% (P < 0.05). It increased both re-endothelialization and endothelial nitric oxide synthase (NOS) expression. Cocktail reduced Egr-1 expression, an effect blocked by the NOS inhibitor L-N G -nitroarginine methyl ester (L-NAME) that also prevented cocktail inhibition of neointima inhibition. Conclusions: This combination may potentially be useful for the treatment of restenosis with concomitant stimulation of revascularization.